Sufyan Al-Tsauri's Interpretation Method in the Perspective of Sunni Interpretation - Muhammad Syamsul Munir; Suqiyah Musafa’ah (Al-Abqori: Journal of Islamic Thought Studies, 2025)
Talking about the interpretation of the Qur'an cannot be separated from the results of the interpretation of a figure. This research is based on a method from Sufyan At-Tsauri which is deep according to the perspective of sunni tafsir. However, basically the dependence of an interpretation of the Qur'anic text by a figure is in terms of the creed adopted. The Qur'anic text is positioned as an open divine creation that opens the possibility to be interpreted by the mufassirs. On the other hand, Tafsir Sufyan At-Tsauri interpreted by Abu Abdillah At-Tsauri was born from the Kuffi group, which is from the city of Kuffah. While the inhabitants of Kuffi are adherents of the Shi'ah faith. That the Shia and Sunni groups are very different, according to the Shi'a creed the concept of Imamah is an imam who comes from the descendants of the Prophet Muhammad SAW through Ali and Fatimah who have the right to lead the Muslim Ummah with a role model in terms of faith after the Prophet SAW. While Sunni or Ahlus Sunnah wal Jama'ah is a group that adheres to the leadership after the Prophet Saw is Abu Bakr as a result of deliberation not from the results of descent unlike the adherents of Shi'ah. This research uses normative which uses data collection methods by means of literature studies on the title of the research. The result of this study is that the concept of Sufyan At-Tsauri's tafsir method emphasizes the Sunni tasfir perspective in interpreting the Qur'an which is written in the work of Tafsir Sufyan At-Tsauri)